The Role of the Mahalawu Studio in the Development of the Jalak Lawu Dance as a Cultural Identity of Magetan Regency - Widarwati Widarwati; Malarsih Malarsih; Eko Sugiarto (Edumaspul: Jurnal Pendidikan, 2024)
The aim of this research is to discuss the role of Sanggar Mahalawu in the development of Jalak Lawu Dance in Magetan Regency. The Jalak Lawu dance is a typical Magetan Regency dance which was created by the Magetan Regency artist, Mrs. Hartini. The development of the Jalak Lawu Dance over time has made the Regency Government, especially the Department of Tourism and Culture and the artists of Sanggar Mahalawu, ask Mrs. Hartini for permission to develop the Jalak Lawu Dance. August 2022 Jalak Lawu Dance was designated as a Typical Dance of Magetan Regency at the same time as the performance building and the Magetan Arts Council (DESIMA) were established. The Jalak Lawu dance is an art that must be preserved as cultural heritage in Magetan Regency. Sanggar Mahalwu is the place where the Starling Lawu Dance began to be taught to the people of Magetan Regency. Efforts to develop the Jalak Lawu Dance continue to be made by Sanggar Mahalwu through learning in the Studio and in schools as well as performances at various important events in Magetan Regency and outside Magetan Regency. As an identity dance, of course the existence of the Jalak Lawu Dance must continue to be pursued both from the cultural and educational sectors.